2020
DOI: 10.2147/jir.s269557
|View full text |Cite
|
Sign up to set email alerts
|

<p>Human Secretary Phospholipase A2 Mutations and Their Clinical Implications</p>

Abstract: Phospholipases A2 (PLA 2 s) belong to a superfamily of enzymes responsible for hydrolysis of the sn-2 fatty acids of membrane phospholipids to release arachidonic acid. PLA 2 s are the rate limiting enzyme for the downstream synthesis of prostaglandins and leukotrienes that are the main mediators of inflammation. The extracellular forms of this enzyme are also called the secretary phospholipase A2 (sPLA 2) and are distributed extensively in most of the tissues in the human body. Their integral role in inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 105 publications
0
14
0
2
Order By: Relevance
“…New studies are needed to identify potential interacting or binding molecules for these enzymes and characterize the resultant downstream signaling. (3) Understanding the mechanisms underlying sPLA 2 expression, secretion, and clearance under normal and pathological conditions would contribute to the development of new strategies to target the sPLA 2 s. (4) Several mutations in sPLA 2 enzymes have been associated with diseases such as atherosclerosis, cardiovascular disease, and asthma [ 65 ]. Recently a rare mutation (R123H) was also identified in sPLA 2 -IIA in two infants with ARDS [ 66 ].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…New studies are needed to identify potential interacting or binding molecules for these enzymes and characterize the resultant downstream signaling. (3) Understanding the mechanisms underlying sPLA 2 expression, secretion, and clearance under normal and pathological conditions would contribute to the development of new strategies to target the sPLA 2 s. (4) Several mutations in sPLA 2 enzymes have been associated with diseases such as atherosclerosis, cardiovascular disease, and asthma [ 65 ]. Recently a rare mutation (R123H) was also identified in sPLA 2 -IIA in two infants with ARDS [ 66 ].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Under these conditions, sPLA2 are often induced together with the C-reactive protein and serve as markers of inflammation [ 76 ]. Studies have identified more than 10 isoforms of sPLA2 e.g., IB, IIA, IIC, IID, IIE, IIF, III, V, X and XIIA, which are distributed among different cell types and body organs [ 77 ]. The ribbon model of human group III sPLA2 showed three helices, one calcium binding loop, five disulfide bonds and His34 and Asp63 in the active site [ 77 ].…”
Section: Structure and Function Of Spla2mentioning
confidence: 99%
“…Studies have identified more than 10 isoforms of sPLA2 e.g., IB, IIA, IIC, IID, IIE, IIF, III, V, X and XIIA, which are distributed among different cell types and body organs [ 77 ]. The ribbon model of human group III sPLA2 showed three helices, one calcium binding loop, five disulfide bonds and His34 and Asp63 in the active site [ 77 ]. In the extracellular milieu, sPLA2s require high levels of calcium for activation [ 78 ].…”
Section: Structure and Function Of Spla2mentioning
confidence: 99%
“…Indole based molecules have been considered in medicinal chemistry. Among those, bis-indole moieties commonly present in numerous drugs with biological actions such as antimicrobial, [55] antifungal, [55] human cancer cell lines, [56] phospholipase A2, [57] anti-inflammatory, [55] coronavirus A-59, [58] a calcineurin inhibitor, [56] anti-serotonin activity, [56] antiviral, [59] antiproliferative, [60] HIV [61] and anti-adipogenic [62] activities. Bisindole methane moieties also present in numerous alkaloids such as Hama Canthin, [63] Dragmacidin, [64] Rhopaladin, [58] Nortopsentin E, [65] Deoxytopsentin, [66] Gelliusines, [67] Dendridine, [68] Caulersin, [69] Caulerpin, [70] Chondriamides [71] and Gelliusin [72] and they are representing numerous biological actions.…”
Section: Introductionmentioning
confidence: 99%